INTERVAL TRAINING IN PHYSICAL REHABILITATION FOR CHRONIC BRONCHI AND LUNG INJURIES (Physical Culture and Sport: Scientific Perspective, 2024)
The problem of respiratory diseases is one of the most pressing in modern clinical medicine. The reasons for the growth of chronic bronchial and lung diseases (decreased working capacity, air pollution and the scale of use of chemical products in production, pandemic, war) are investigated. The ways of increasing morbidity and mortality due to chronic obstructive pulmonary disease (COPD) and chronic bronchitis (CB), which significantly affects socio-economic indicators, are revealed. It has been shown that the disease with predominant damage to the airways is associated with inflammation or prolonged irritation of the bronchial mucosa by various agents, characterized by a progressive and recurrent course; that occurs over a long period of time, in which the mucous membrane is affected first, then the deeper layers of the bronchial walls and peribronchial connective tissue. A program of physical rehabilitation of patients with chronic bronchial and pulmonary disease using repeated training was developed: massage according to the classical method, performing surface breathing according to the method of O.V. Peshkova, as well as interval training method of running and walking. It is proved that the application of the developed program of physical rehabilitation with interval training in clinical practice shows the advantages of the developed methodology in chronic bronchial and pulmonary diseases.The application of the developed physical rehabilitation program in clinical practice shows the advantages of the developed technique in chronic lesions of the bronchi and lungs.The problem of the use of intensive training in physical therapy for diseases of the respiratory organs remains unresolved.
Keywords: respiratory system; method of repeated training; patients